Intervertebral Disc Degeneration and Low Back Pain: Molecular Mechanisms and Stem Cell Therapy - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2018)
BACKGROUND: Low back pain (LBP) mostly caused by disc degeneration, reflects to a tremendous of health care system and economy. More knowledge about these underlying pathologies will improve the opportunities that may represent critical therapeutic targets.CONTENT: Basic research is advancing the understanding of the pathogenesis and management of LBP at the molecular and genetic levels. Cytokines such as matrix metalloproteinases, phospholipase A2, nitric oxide, and tumor necrosis factor-α are thought to contribute to the development of LBP. Mesenchymal stem cells (MSCs) transplant to cartilage-like cells and secrete extracellular matrix and encourage nucleus pulposus (NP) cell activity inhibiting NP cell apoptosis, together with some chemical mediators such as cytokines and growth factors become a safe and effective new strategy for intervertebral disc degeneration (IDD) treatment and regeneration.SUMMARY: IDD occurs where there is a loss of homeostatic balance with a predominantly catabolic metabolic profile. A basic understanding of the molecular changes occurring in the degenerating disc is important for practicing clinicians to help them to inform patients to alter lifestyle choices, identify beneficial or harmful supplements, or offer new biologic, genetic, or stem cell therapies.KEYWORDS: low back pain, intervertebral disc, degeneration, nucleus pulposus, annulus fibrosus, extracellular matrix, genetic, stem cells